Reference-Dependent Preferences, Time Inconsistency, and Unfunded Pensions - Torben M. Andersen; Joydeep Bhattacharya; Qing Liu (Center for Economic Studies and ifo Institute (CESifo), 2020)
In the real world, public pay-as-you-go pension (PAYG) schemes are popular and co-exist with private, retirement-saving schemes. This is true even in dynamically efficient economies where such pensions offer a lower return. The classic Aaron-Samuelson result argues that, in theory, this is impossible. Later work has shown that it may be possible if agents, left on their own, undersave due to myopia or time-inconsistency. In that case, if the government is paternalistic, a welfare rationale for PAYG pensions arises but only if voluntary retirement saving is fully crowded out because of a binding borrowing constraint. This paper generalizes the Aaron-Samuelson discussion to the reference-dependent utility setup of Kőszegi and Rabin (2009) where undersaving happens naturally. No borrowing constraint is imposed. In this case, it is possible to offer a non-paternalistic, welfare rationale for return-dominated, PAYG pensions to coexist with private retirement saving.
Keywords: H55; E60; 330; reference-dependence; crowding-out; pensions; dynamic efficiency